(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
This study examined the effects of the Multiplication Turn-Table instructional material on the multiplication skills of third-grade students at San Bartolome Elementary School. A total of 50 respondents participated, with 20 from Section Narra and 30 from Section Kamatsile. To measure students’ multiplication skills before and after the intervention, the researchers developed and administered a pre-test and post-test. This study employed a causal-comparative design, with 50 students from San Bartolome Elementary School selected through purposive sampling. A pre-test and post-test were administered to gather the necessary data. The researchers analyzed the results using statistical tools, including percentage, weighted mean, and Z-test, to evaluate the effectiveness of the Multiplication Turn-Table instructional material. The findings revealed that 75% of the respondents were aged 8–9 years old, and 83% were male. A comparison of pre-test and post-test scores was conducted to assess performance. During the pre-test, mean scores were 8.34 and 2.80, while in the post-test, mean scores were 8.26 and 3.30. The results indicated that Grade 3 students at San Bartolome Elementary School showed significant improvement in their multiplication skills after using the Multiplication Turn-Table instructional materials. The turntable was found to support various learning styles and enhance numeracy skills. However, challenges were noted, such as the need to strengthen connections between multiplication and real-world math applications. To further improve students’ skills, the researchers recommend integrating theoretical knowledge with practical activities, incorporating interactive and age-appropriate materials, and providing regular feedback from instructors. Based on the results, teachers are encouraged to use turn-tables to address different learning styles and guide students in effectively using instructional materials. Parents can make multiplication more engaging by incorporating games, quizzes, and prizes into learning activities. Students should be encouraged to actively participate, explore concepts, and apply their knowledge in real-world situations. School administrators are advised to align instructional materials with the curriculum, provide training sessions for teachers, and ensure adequate resources are available for all learners. For future research, studies could examine the effectiveness of similar instructional tools in developing mathematical skills, allowing for comparisons and identification of emerging trends.